Beyond the Eyelid: Congenital Upper Eyelid Coloboma with Palpebro-Corneo-Conjunctival Adhesion in an Infant - Felicia Fortunata; Yana Rosita; Dini Dharmawidiarini (Vision Science and Eye Health Journal, 2026)
Introduction: Congenital eyelid coloboma is a rare structural lid defect extending through all layers of the eyelid, with the potential to threaten the ocular surface and visual development. When accompanied by palpebro-corneo-conjunctival adhesion, surgical complexity increases substantially, as both eyelid reconstruction and corneal repair must be addressed concurrently. Case Presentation: An 11-month-old boy presented with a left upper eyelid coloboma since birth, with two-thirds palpebro-corneo-conjunctival adhesion extending to the posterior corneal stroma. Posterior lamellar reconstruction combined with anterior lamellar keratoplasty was performed under general anesthesia. At postoperative day one, sutures were intact with good graft apposition and minimal corneal edema. At day 11, the corneal graft was clear and well epithelialized with no signs of rejection. At four months, the graft remained intact; however, corneal clarity could not be fully assessed as the procedure was performed primarily for tectonic purposes. Margin reflex distance 1 (MRD1) was not obtainable due to an absent corneal light reflex secondary to corneal opacity. The reconstructed eyelid demonstrated good anatomical contour and stable position. Conclusions: This case demonstrates that combining posterior lamellar reconstruction with anterior lamellar keratoplasty is feasible in infants with extensive eyelid coloboma and corneal adhesion, with stable outcomes at four months postoperatively. The limited follow-up duration in this case does not yet allow for a definitive assessment of long-term graft outcomes. Ongoing monitoring by a multidisciplinary team, including a pediatric ophthalmologist for amblyopia surveillance and a glaucoma specialist for intraocular pressure assessment, will be critical going forward.